Strength and plasticity of amorphous ceramics with self-patterned nano-heterogeneities. (November 2020) - Ming, Kaisheng; Gu, Chao; Su, Qing; Xie, Dongyue; Wu, Yaqiao; Wang, Yongqiang; Shao, Lin; Nastasi, Michael; Wang, Jian
Abstract: Amorphous ceramics with superb strength and irradiation tolerance are promising candidate materials for nuclear industry. However, the brittle-like behavior extremely limits their applications. Here, we demonstrate that Fe–SiOC amorphous ceramic composites (ACCs) with self-patterned Fe-rich nanoclusters fabricated by co-sputtering Fe and amorphous SiOC ceramic not only exhibits exceptional, homogeneous plasticity at room temperature but also remains high strength and good irradiation tolerance. Flow strength of Fe–SiOC ACCs decreases but plasticity increases with the increase in Fe content. Moreover, the strength and plasticity of Fe–SiOC ACCs can be further tailored by subsequent annealing and ion irradiation associated with the change in their microstructure. High temperature annealing tunes amorphous Fe-rich nanoclusters into crystalline Fe nanoparticles, significantly enhancing flow strength of Fe–SiOC ACCs without loss of plasticity. Ion irradiation does not apparently modify the microstructure and reduce plasticity of Fe34at.%-SiOC ACC, but slightly enhances their flow stress. For instance, annealed Fe34at.%-SiOC ACC has flow true stress exceeding 4.0 GPa at a large uniform compressive strain of 55% without plastic flow instability and cracking. The spatially distributed Fe-rich heterogeneities (amorphous nanoclusters and crystalline nanoparticles) plastically co-deform with amorphous SiOC matrix and discretize shear transformation zones in amorphous ceramics, thus preventing the shear-banding instability and significantly enhancing compressive plasticity. The plastic co-deformation between Fe-rich nano-heterogeneities and amorphous SiOC ceramic matrix is achieved due to interface constraint, preventing cracking and ensuring homogeneous plastic deformation of Fe–SiOC ACCs. These findings suggest that patterning nanoscale metal-rich heterogeneities can tailor mechanical properties of amorphous ceramics. Graphical abstract: Image 1 Highlights: Fe-SiOC amorphous ceramic composite (ACC) with self-patterned Fe-rich nanoclusters are fabricated by co-sputtering. Flow strength of Fe-SiOC ACCs decreases but plasticity increases with the increase in Fe content. High temperature annealing tunes amorphous into crystalline nanoparticles, strengthening without loss of plasticity Ion irradiation does not apparently modify the microstructure, but enhances flow stress without loss of plasticity. Nano-heterogeneities plastically co-deform with SiOC matrix, preventing shear instability.